Efetividade da higienação de brinquedos infantis quando comparada a nenhuma intervenção na redução de infecções microbianas em ambientes relacionados ao cuidado de crianças: revisão sistemática da literatura - Blasi, Débora Guedelha [UNESP] (2015)
Toys belong to the infant universe and are objects much shared by children, parents, health professionals and educators. Considering the hands as the reservoir of microorganisms, toys become transmission vehicles of bacteria, fungi and viruses. The objective of this work is to assess the effectiveness of the sanitation of infant toys, when compared to no intervention in the reduction of the microbial load in environments where the care of children exists. It is a systematic review of the literature in the last ten years, held through the bases of electronic data and through dissertation banks and theses, using structured search strategy and pre-established criteria. The obtained data were tabulated and submitted to the analysis of subgroups, which was done descriptively due to the methodological variability of the raised researches. Twelve researches were raised which fitted in the criteria of inclusion. Predominant were the comparative researches of the microbial loads before and after the intervention of the sanitation of the toys. The researches were divided into subgroups according to the composition of the studied toy, and the results presented different interventions of sanitation not existing works that have used identical methods of sanitation for toys of the same composition. The raised works showed low level of scientific evidence, and the methods of sanitation were much varied, thus hampering comparisons, crossing of the results and selection of a more effective method. Issues regarding child safety in relation to the product used for the sanitation among the raised researches ...